Adding Paracetamol to Ibuprofen for the Treatment of Patent Ductus Arteriosus in Preterm Infants: A Double-Blind, Randomized, Placebo-Controlled Pilot Study - Hochwald, Ori; Mainzer, Gur; Borenstein-Levin, Liron; Jubran, Huda; Dinur, Gil; Zucker, Meirav; Mor, Malka; Khoury, Asaad; Kugelman, Amir (American Journal of Perinatology, 2018)
Objective The objective of this study was to compare the closure rate of hemodynamically significant patent ductus arteriosus (hsPDA) of intravenous ibuprofen + paracetamol (acetaminophen) versus ibuprofen + placebo, in preterm infants of 24 to 316/7 weeks postmenstrual age.Study Design This is a single-center, double-blind, randomized controlled pilot study. Infants were assigned for treatment with either intravenous ibuprofen + paracetamol (n = 12) or ibuprofen + placebo (n = 12).Results There was no statistical difference in baseline characteristics of the two groups. Echocardiography parameters were comparable before treatment in both groups. There was a trend toward higher hsPDA closure rate in the paracetamol group in comparison to the placebo group (83 vs. 42%, p = 0.08). No adverse effects, clinical or laboratory, were associated with adding paracetamol.Conclusion Our pilot study was unable to detect a beneficial effect by adding intravenous paracetamol to ibuprofen for the treatment of hsPDA. Larger prospective studies are needed to explore the positive tendency suggested by our results and to assure safety.
Keywords: nonsteroidal anti-inflammatory drugs; premature; neonate; hemodynamically significant patent ductus arteriosus; paracetamol; ibuprofen; echocardiography